ANALISIS SENTIMEN TERHADAP DAMPAK PERANG ISRAEL - PALESTINA MELALUI DATA TWITTER MENGGUNAKAN NAIVE BAYES - Halim, Alfian Noer; Dwiasnati, Saruni (Universitas Mercu Buana, 2024)
The increasing development of information technology makes it easy for people to get various information only through social media such as Twitter. Twitter is a mainstay social networking application and source of information on world events. With Twitter, people can get a lot of the latest news. One piece of information that is widely discussed and is a trending topic on Twitter is the impact of the Israeli and Palestinian war. It is important to analyze the feelings of the impact of the ceasefire between Israel and Palestine from the amount of information in online media. The data used is Twitter, a social media platform. This research was conducted to analyze people's reactions to data in the form of tweets and group them according to the Naïve Bayes method into positive, neutral or negative opinions. In implementing the Naïve Bayes algorithm which uses 3 models of the Naïve Bayes algorithm, namely Gaussian, Multinomial, and Bernoulli, it shows different results, namely 50% for the Naïve Bayes Gaussian model, 57% for the Naïve Bayes Bernoulli model, and Naïve Bayes Multinomial model is 65 %. This shows that the Multinomial Naïve Bayes model is better than other models in classifying the data in this case.